2005
DOI: 10.1088/6102/44/4/646
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous Bethe–Salpeter Equation and Its Analog: Breit-like Equation

Abstract: We take (µ ± e ∓ ) systems and consider the states with quantum number J P = 0 − as examples, to explore the different contents of the instantaneous Bethe-Salpeter (BS) equation and its analog, Breit equation, by solving them exactly. The results show that the two equations are not equivalent, although they are analogous. Furthermore, we point out that the Breit equation contains extra unphysical solutions, so it should be abandoned if one wishes to have an accurate description of the bound states for the inst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Details about examining the equivalence may be found in ref. [10]. Alternately here we exactly start with the four equations to solve the BS-In equation.…”
Section: Instantaneous Bethe-salpeter Equationmentioning
confidence: 99%
“…Details about examining the equivalence may be found in ref. [10]. Alternately here we exactly start with the four equations to solve the BS-In equation.…”
Section: Instantaneous Bethe-salpeter Equationmentioning
confidence: 99%
“…III. V 1 and V 2 are the scalar confinement and one-gluon-exchange terms given in the following, respectively, (after imposing covariant instantaneous approximation [41][42][43][44]):…”
Section: Bs Equation For Doubly Heavy Baryonsmentioning
confidence: 99%
“…In the numerical calculations, we let 0 vary between 0:01 GeV 3 and 0:06 GeV 3 [8,39,49]. The light quark propagator can be written as the following form [9,44]:…”
Section: Bs Equation For Doubly Heavy Baryonsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Cartesian coordinate system this mixing cannot be separated clearly, especially for high spin bound states, for example 2 + , 2 ++ , etc. We found that it can be done in spherical coordinate system [13,16,17]. …”
Section: The Salpeter Wave Functionmentioning
confidence: 99%